Characteristic Soil Chemical Properties and Water On Tea Garden Alahan Panjang Region - sri dewi murni (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
This study was to determine and measure the chemical characteristics of environmental soil in tea gardens in Alahan Panjang. The research was conducted in Alahan Panjang, West Sumatra for soil and water sampling and analyzed at the Agricultural Laboratory of Andalas University.Soil samples was taken in a composite manner at a depth of 0-20 cm. Parameter analysed werepH of H2O, total soil N, soil organic C, available P, K-dd, pH H2O (5.62), C-organic (4.43), N-total, (1.23), P-available (46.43), KTK (15.50), (K-dd 0.37). The result showed the value of chemical properties is obtained water pH H2O (5.62), C-organic (4.43), N-total, (1.23), P-available (46.43), KTK (15.50), (K-dd 0.37). Analysis of water obtained pH H2O (6.64,) N-total (2.45 mg / l), P-available (0.23), K-dd (0.21).